The Impact of Leadership Development Programs on The Performance of Educational Leaders - Haiou, Zou; Anuar, Nurwina; Mansor, Ahmad Zamri (South Asian Journal of Social Sciences and Humanities, 2025)
Educational leadership development programs are important to develop the abilities and competence of academic leaders to foster institutional success. This study explores the impact of such programs on leadership competencies, decision-making, and overall performance in educational situations. Research identifies such factors by examining different training methods, such as mentorship, workshops, and experiential learning, influencing leadership growth. These findings offer valuable guidance to policymakers and educators to provide more dynamic and results-driven leadership training to improve the quality of an educational environment.
Keywords: Leadership development; educational leaders; performance; training programs; institutional effectiveness